2022
DOI: 10.1021/acsami.2c12034
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Surface Functionalization of Polyacrylamide Hydrogels Below the Length Scale of Hydrogel Heterogeneity

Abstract: Hydrogels are broadly used in applications where polymer materials must interface with biology. The hydrogel network is amorphous, with substantial heterogeneity on length scales up to hundreds of nanometers, in some cases raising challenges for applications that would benefit from highly structured interactions with biomolecules. Here, we show that it is possible to generate ordered patterns of functional groups on polyacrylamide hydrogel surfaces. We demonstrate that, when linear patterns of amines are trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…We have discovered that a similar in situ polymerization process enables sPDA transfer to acrylate hydrogels (Fig. 9a), 13 with transfer dependent upon gel composition (Fig. 9b).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…We have discovered that a similar in situ polymerization process enables sPDA transfer to acrylate hydrogels (Fig. 9a), 13 with transfer dependent upon gel composition (Fig. 9b).…”
Section: Introductionmentioning
confidence: 89%
“…1,[6][7][8][9][10][11] We then describe surface patterning strategies based on noncovalent molecular network assembly on hard 2D materials, which can be used to produce nanometer-resolution chemical patterns, with a particular focus on striped phases of photopolymerizable functional alkanes. Recently, we have observed that chemical patterns embedded in these molecular layers can be transferred to the surfaces of soft materials including PDMS and hydrogels, 12,13 so we additionally discuss the outcomes of transferring high-resolution functionality to pattern amorphous materials below the length scale of their structural heterogeneity, and applications of this approach.…”
Section: Anni Shimentioning
confidence: 99%
See 1 more Smart Citation
“…These research methods have great implications for the synthesis of multicolor UCNPs. UCNP ink has been widely reported, but a large amount of luminescent ink dissolved in organic solvents, or containing toxic ions, hinders its application in food and medicine. , To broaden the scope of UCNP applications, poly­(vinyl alcohol), gelatin, and polyacrylamide (PAM) materials instead of ink, combined with UCNPs, are used to achieve an environment-friendly luminescent gel. Such luminescent gels are biocompatible, nontoxic, , and degradable, , which can mitigate pollution and safety issues and are highly compatible with the current concept of carbon neutrality. Recently, Li et al used lanthanide complexes combined with hydrogels to construct three-dimensional (3D) information codes and realized the encryption and interpretation of luminescence information by simply alternating exposure to ultraviolet (UV) light and visible (vis) light .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, surface processing of polymers has significant importance today. In particular, there is an interest in generating nanostructures with complex morphologies in polymers or polymer-based composites to produce functional surfaces [ 15 , 16 ]. The nanostructures generated in these materials may have interesting wettability properties for applications, such as the prevention of frost formation [ 17 ] or water harvesting [ 18 ], or adhesion properties that mimic characteristics exhibited by some living beings in nature [ 19 ].…”
Section: Introductionmentioning
confidence: 99%